MECHANISM OF MOTION IN WIJAYA KUSUMA FLOWER PLANT (Epiphyllum anguliger): QUEEN OF THE NIGHT AS A SOURCE OF LEARNING PLANT PHYSIOLOGY - Umi Rahmah Wuryan Timur; Pramita Laksitarahmi Isrianto; Marmi Marmi; Sunaryo Sunaryo (Journal of Natural Sciences and Learning, 2023)
Plants or plants are living things just like humans and animals. Plants also move which aims to show irritability and to respond to the stimuli it receives. Movement in plants is divided into several categories, one of which is the motion of tropism, which is also divided into more specific movements. This writing aims to find out and study the mechanism of motion of the wijaya kusuma flower. Wijaya Kusuma Flower Plants are plants that have special movements and are different from the movements of other plants. Most people do not know that the movement of the wijaya kusuma flower plant is called scototropism. This motion can also be said to be negative phototropism because the plant will move away from the sun when the light comes close to the plant. One of the characteristics of the Wijaya Kusuma flower itself is that it can only bloom at night for between 1 and 2 hours and will wither the next morning.